Image Recognition using Visual Features - Mente, Rajivkumar; Dhandra, BV (International Journal of Computer Sciences and Engineering, 2014)
Content-based image retrieval (CBIR) is a method which uses visual contents to seek images from large size image databases according to the choice of the users. Human intervention in the text based image retrieval makes the system cumbersome, labor intensive and time consuming. Hence, there is a need to design the algorithms to retrieve the desired images from the database without human intervention, to enable for fast, accurate and reliable retrieval of the desired images. The challenge of the CBIR system is to identify the suitable features of images to retrieve image from image database. The algorithm presented in this paper uses color, texture and shape features to form the feature vector of training images and test images. These feature vectors and the k-NN classifier is used to search the test image in the database of training images. A database of 2732 fruit images from six different classes is used to test the proposed algorithm. The higher recognition accuracy achieved for the proposed algorithm is 98.43%.